THE EFFECT OF THE SELF-SUPERVISION MODEL INTEGRATING AUTHENTIC MOVEMENT AND EPIMOTORICS' ON SELF-EFFICACY AMONG DANCE MOVEMENT THERAPISTS - Yifat SHALEM-ZAFARI; Emilia Florina GROSU (Cluj University Press, 2017)
Introduction: This study is part of a larger research study examining the effect of a unique model of self-supervision based on Authentic Movement and Epimotorics' on young therapists. It relies on one of the basic assumptions in dance/movement therapy - that psychological/emotional states are reflected in one's manner of movement and body positions, and also that the position and movement of the body influence a person's emotional/ psychological state (Shahar-Levy, 2004; Chaiklin, 2009). This study attempted to demonstrate that the unique self-supervision model would change the sense of self-efficacy of young dance/movement therapists. Supervision in this field bases itself on moving between verbal language and body-movement language, and uses both languages as a source for cognitive and psycho-emotional language knowledge (Payne, 1992; Shalem-Zafari, 2016). Methods and Materials: This study utilized film-recordings for observation, the Epimotoric's movement-analysis tool, and questionnaires: Epimotorics' is a method of movement observation and analysis, which relates to visible human movement as "telling" the internal psycho-emotional scenario. The self-efficacy questionnaires that were used provide information about the way the therapists' view their own effectiveness and abilities. Results: It was found that the self-supervision model stimulated changes in the movement measures of the participants and showed marginally significant positive change in their self-efficacy. Conclusion: It can be suggested that the self-supervision model combining verbal and non-verbal movement languages allows for the use of knowledge stored in the body in combination with cognitive, verbal language. As such, it improves the therapists' experience in relation to their sense of professional capability.